Expansion of WINFA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Expansion of WINFAThe Windward Islands Farmers' Association (WINFA) will be opening its membership for expansion. According to WINFA's coordinator Renwick Rose, the expansion of its membership will increase representation of various farmers' groups...